Definitive Radiotherapy in Invasive Vaginal Carcinoma: A Systematic Review. (23rd August 2018) - Guerri, Sara; Perrone, Anna M.; Buwenge, Milly; Ferioli, Martina; Macchia, Gabriella; Tagliaferri, Luca; Ferrandina, Gabriella; Galuppi, Andrea; Andrulli, Angela D.; Frakulli, Rezarta; Cammelli, Silvia; Arcelli, Alessandra; et al.
Abstract: Aim: This study systematically reviews the recent literature on the role of definitive radiotherapy (RT) in the management of vaginal cancer (VC) and presents comprehensive data on clinical outcomes and toxicity. Methods: The authors performed a literature search using PubMed (2007–2016) to identify all prospective and retrospective studies that have been published on RT in invasive VC. Results: Of the 199 identified studies, 13 met the inclusion criteria. All studies had a retrospective design. Overall, 793 patients (median, 45; range, 26–138) were included. A high heterogeneity was found across studies in terms of RT techniques, assessment criteria, and reported outcomes. The majority of the patients were treated with a combination of external beam RT and brachytherapy (74.2%). Acute and late grade ≥3 toxicity rates ranged from 0.0% to 24.4% (median, 8.7%) and from 0.0% to 22.5% (median, 12.8%), respectively. The 5‐year local control rates ranged between 39% and 79%. The 5‐year overall survival ranged between 34% and 71.0% (median, 63.5%). Early stage of the disease (International Federation of Gynecology and Obstetrics stages I–II vs. III–IV), small tumor size (<4 cm), previous hysterectomy, high pretreatment/treatment hemoglobin levels (≥12/12.5 mg/dL), and patients' age <70 or <64 years were correlated with better clinical outcomes. Conclusion: Only retrospective studies, in a limited number, have been published on RT in VC in the past decade, with significant heterogeneity in terms of treatment characteristic and evaluation criteria. Clinical results were strongly influenced by tumor stage. Prospective randomized studies are needed to improve patients' outcomes, especially in advanced‐stage disease. Implications for Practice: This study systematically reviews the recent literature on the role of definitive radiotherapy in the management of vaginal cancer and presents comprehensive data on clinical outcome and toxicity. The prognosis of patients is dismal, with a 5‐year overall survival of approximately 50%. Early stage of the disease, small tumor size, previous hysterectomy, high pretreatment/treatment hemoglobin levels, and patients' age were correlated with a better clinical outcome. A brachytherapy boost should be delivered, especially in patients with higher‐stage disease. The addition of concurrent weekly cisplatin should be considered in most patients, and transfusion should be used to maintain high hemoglobin levels. Abstract : This systematic review provides an overview of the role of radiation therapy in the management of vaginal carcinoma and summarizes data on treatment outcome and toxicity.